The role of phonemic verbal fluency test on the assessment of cognitive performance in multiple sclerosis - Sousa, C.; Neves, M.; Passos, A. M.; Ferreira, A.; Sá, M.J. (3rd International Porto Congress of Multiple Sclerosis, 2015)
Executive dysfunction occurs in 15 to 20% of Multiple Sclerosis (MS) patients. They usually report subjective complaints characterized by generalized cognitive inefficiency featured by a reduced verbal fluency, like “losing the thread of conversation” [1]. The verbal fluency tests provide brief and sensitive measures of these deficits and they involve associative exploration and retrieval of words based on phonemic or semantic criteria (phonemic and semantic fluency) [2]. The Word List Generation (WLG) is one of the most commonly used phonemic verbal fluency measures in MS. Many studies show that performance of MS patients on phonemic verbal fluency tests have been consistently lower than healthy controls, suggesting that MS patients were substantially impaired on this measure [3]. Some studies also suggest that the verbal fluency test is one of the most sensitive measures of cognitive impairment in MS, along with the Symbol Digit Modalities Test (SDMT) [4].